2016
DOI: 10.4103/1319-2442.182389
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperoxaluria in infants

Abstract: The infantile form of primary hyperoxaluria type-1 (PH-1) is characterized by a rapid progression to the end-stage renal disease (ESRD) due to both increased oxalate load and reduced glomerular filtration rate. In the literature, data on this form are limited. The purpose of this study is to analyze retrospectively the clinical, biological, and radiological features of children who were diagnosed with PH-1 during the 1(st) year of life. We reviewed the records of all children with PH-1 diagnosed and followed-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…To the best of our knowledge, we demonstrate for the first time the irreversible course of ROx despite early CLKT in patients with IO disease even after a follow‐up of more than 10 years. It is well known, that IO represents the most severe subgroup of PH1 patients, with high mortality and morbidity . However, we have shown that results of CLKT are encouraging, especially that deposition of oxalate into bone decreases after CLKT leading to normal growth .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, we demonstrate for the first time the irreversible course of ROx despite early CLKT in patients with IO disease even after a follow‐up of more than 10 years. It is well known, that IO represents the most severe subgroup of PH1 patients, with high mortality and morbidity . However, we have shown that results of CLKT are encouraging, especially that deposition of oxalate into bone decreases after CLKT leading to normal growth .…”
Section: Discussionmentioning
confidence: 99%
“…Primary hyperoxaluria type 1 (PH1) is a rare genetic autosomal recessive condition (1-3 per million) characterized by oxalate deposition in the kidneys as calcium oxalate stones due to a deficiency in the liver enzyme alanine glyoxylate aminotransferase. This results in nephrocalcinosis and eventually end stage renal disease (ESRD) [1] , [2] , [3] . Definitive diagnosis is obtained through genetic testing.…”
Section: Introductionmentioning
confidence: 99%
“…As the disease progresses to ESRD, patients will eventually require liver and kidney transplantation [3] . In infants, PH1 frequently presents with failure to thrive (FTT) in the setting of ESRD [ 1 , 2 ]. We describe the initial presentation of hyperoxaluria without renal compromise, complicated by severe FTT that did not respond to standard interventions.…”
Section: Introductionmentioning
confidence: 99%
“…When AGT activity is deficient, glyoxylate is converted to oxalate, which then forms insoluble calcium salt deposits in the kidney and other organs (Williams et al, 2009). Human PH1 can be classified into the following forms according to clinical severity: the infantile form with early renal insufficiency, the late-onset form with a good prognosis, and the most common form with recurrent urolithiasis or nephrocalcinosis that is usually accompanied by renal insufficiency (Jellouli et al, 2016). The infantile form is the most severe (Jellouli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Human PH1 can be classified into the following forms according to clinical severity: the infantile form with early renal insufficiency, the late-onset form with a good prognosis, and the most common form with recurrent urolithiasis or nephrocalcinosis that is usually accompanied by renal insufficiency (Jellouli et al, 2016). The infantile form is the most severe (Jellouli et al, 2016). The genetic basis for PH1 has been identified in at least 190 published AGXT gene (coding AGT) mutations (Coulter-Mackie et al, 1993–2017; Isiyel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%